Analisis Nilai Pentanahan di Auditorium Kampus 2 UKI Toraja - Defri Nadus; Martina Pineng; Ishak Pawarangan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2024)
The grounding system aims to secure electrical equipment and humans. This study was located around the Auditorium area of UKI Toraja Campus 2 which does not yet have a grounding system. One of the factors to get a small grounding value is the location of the electrode to be planted and to determine the resistance value, measurement is needed. Data analysis consists of calculating the depth of the electrode and several grounding points, with the method that will be carried out in this grounding is grounding the rod with 3 measurements. In this measurement, the depth is 30 cm, 60 cm, and 90 cm. With a minimum and maximum resistance value of 30 cm, respectively 3.85 Ohm and 57.10 Ohm, the minimum and maximum resistance value of 60 cm is 2.35 Ohm and 34.52 Ohm, respectively, the minimum and maximum resistance value of 90 cm depth. also 1.69 Ohms and 24.07 Ohms. The value of ground resistance that meets PUIL 2011 standards at the Auditorium Campus 2 UKI Toraja for a depth of 30 cm is found at 2 points, a depth of 60 cm has 6 points and a depth of 90 cm has 10 points.